(untitled) (Journal of the College of Basic Education, 2023)
The research aims to reveal the geographical factors that contributed to the settlement of these factories in the city of Bani Saad in Diyala Governorate, as well as to study the spatial analysis of the factories that stopped working in the study area. The research assumes that there is spatial variation in the geographical distribution of the discontinued factories in the city of Bani Saad, and geographical factors had an important role in this distribution. The structure of these industries and their geographical distribution and the problems they suffer from through the data and information that the study signed based on the method of the field study and then analyzed using maps and tables and in accordance with the methodology of the study in order to reach the reality of the political, security and economic changes that led to the cessation of these factories. The research assumes that the stopped industrial factories had an important contribution to the national economy, that the political, security and economic conditions were a major reason for stopping these factories as a result of the conditions that Iraq went through in general, such as wars and siege, and the accompanying political, security and economic instability, economic interventions and foreign policy, all of these Conditions and problems contributed to the suspension of these laboratories. It was found from the study of the industrial structure of the stopped factories in the study area that they had acquired important industrial branches such as the chemical, food, metal, construction industries, textiles, clothing, leather, wood, paper and electricity. These industries constitute the basic base for the manufacturing sector in any country. As for the most important recommendations, they were: 1- Supporting newly established small industrial establishments by granting facilities and loans, as well as tax exemptions imposed on new establishments and investors. 2- The need for the statistical and planning departments in the governorate to pay attention to collecting statistical data on industrial activities, which includes realism and reflects the reality of those activities.